NUMERICAL ANALYSIS OF AIR COOLED PASSIVE CONTAINMENT COOLING SYSTEM CHARACTERISTIC AT AP1000 MODEL - ANGGRAINI, DWITYA
In these recent years, electricity supply crisis in Indonesia happens very often. One of the alternative energy that is offered is nuclear power plant. One of its safety features is PCS (Passive Containment Cooling System). The objective of this research is to make numerical analysis of PCS air cooled characteristic at AP1000 model using CFD (Computational Fluid Dynamics) and natural convection approach. This research started with study about AP1000 and also study about GAMBIT and FLUENT. The next step was to make a model similar to the real containment and meshed it using GAMBIT. Then, meshed model was exported to FLUENT for numerical analysis. This research was intended to get convection heat transfer coefficient. The next analysis was done to search equations of correlation in form of non-dimensional numbers and critical heat fluxes. This final project also explained the effects of variety of air baffle’s width and containment height. Based on numerical investigation, presence of air baffle inside the containment increased heat transfer and a better cooling system was achieved. Unfortunately, there is a time when PCS cannot work properly anymore, it happened when heat fluxes which came through the containment wall reached its critical limit or cooler air was obstructed. Critical heat fluxes was reached when the mean temperature of wall containment was 548,598 K (heat fluxes=838,692 W/m2) for no baffle model 395,672 K (heat fluxes=1118,256 W/m2) for baffled model. Amount of heat transfer coefficient would be decrease if air baffle was too narrow or too wide. Heat transfer reached maximum at 2 cm air baffle’s width or same as 0.8 m at real containment.